Some Further Study Based on Cohen’s Kappa Statistic: Theory and Applications - Yimprayoon, Pornpis (Agriculture and Natural Resources, 2014)
The statistical inference of the problem of measuring agreement between two raters who employ measurements on a two-point nominal scale was studied. The objective was to propose some further characteristics on Cohen’s kappa statistic. Another approach was proposed to test whether or not the observed estimate of kappa is significantly greater than a high predetermined value for a given value of an observed agreement. Moreover, the proposed test procedure was illustrated using a real data example.